Analysis of Water Availability at Margatiga Dam - Ega Rizky Setyawanto; Dyah Ari Wulandari (TEKNIK, 2025)
A dam is a structural construction built to retain or store water and serves to distribute water for raw water supply, irrigation, and hydroelectric power generation. Margatiga Dam is the third and most downstream dam in the Sekampung River Cascade Dam System in Lampung Province. It functions to supply irrigation and raw water as well as to control floods. To meet water demand, an analysis of water availability is necessary to determine the difference between water availability and demand. This study aims to determine the water availability discharge during wet, normal, and dry years at Margatiga Dam. The study uses satellite rainfall data calibrated with ground station rainfall data from 2001 to 2023. The methods used include satellite rainfall data correction, potential evapotranspiration analysis using the modified Penman method, flow discharge analysis using the F.J. Mock method, and reliable discharge analysis using the Weibull method. The results show that the water availability discharge at Margatiga Dam is 13.96 m³/s in a wet year, 10.34 m³/s in a normal year, and 8.13 m³/s in a dry year.